Product identification of non-reducing polyketide synthases with C-terminus methyltransferase domain from Talaromyces stipitatus using Aspergillus oryzae heterologous expression. Issue 7 (1st April 2015) - Hashimoto, Makoto; Wakana, Daigo; Ueda, Miki; Kobayashi, Daisuke; Goda, Yukihiro; Fujii, Isao
Graphical abstract: Abstract: Talaromyces stipitatus ATCC 10500 possesses 17 non-reducing polyketide synthase (NR-PKS) genes. During the course of our functional analysis of PKS genes with a C-terminus methyltransferase domain from T. stipitatus, we expressed tspks2, tspks3 and tspks4 genes in the heterologous host Aspergillus oryzae, respectively. Although the tspks4 transformant gave no apparent product in HPLC analysis, a novel azaphilone pentaketide (3 ) was identified along with two known related products from the tspks2 transformant. Of four hexaketide products from the tspks3 transformant, two new compounds were identified to be 2-acetyl-7-methyl-3, 6, 8-trihydroxynaphthalene (4 ) and its derivative fused with α-methyl-α, β-unsaturated γ-lactone (7 ).